A Comparative Study of Sol–Gel Synthesized ZnO/GO and ZnO/g-C3N4 Nanocomposites in the Photocatalytic Degradation of Acetaminophen - Judith Chebwogen; Francis W. Nyongesa; Julius M. Mwabora; Gershom M. Ntshani; Patrick G. Ndungu (International Journal of Photoenergy)
The large surface area for pollutant adsorption and low charge recombination exhibited by carbon-based nanocomposites enhances the performance efficiency of photocatalysts. Herein, the performance of ZnO/GO and ZnO/g-C3N4 nanocomposites in the photocatalytic degradation of acetaminophen under UV irradiation was compared. The nanocomposites were synthesized by a facile sol–gel method. The structural, morphological, and optical properties were studied using XRD, SEM, TEM, FTIR, BET, UV-Vis, and PL characterization techniques. An increase in surface area was observed with the introduction of GO and g-C3N4. The ZnO/g-C3N4 nanocomposites possessed a greater surface area and photocatalytic efficiency than the ZnO/GO nanocomposites. The degradation efficiencies obtained were 84.6% and 61.2% for the best ZnO/g-C3N4 and ZnO/GO nanocomposites, respectively, in 1 μg/mL acetaminophen degradation at pH 7, hence their great potential for environmental remediation applications.